PENGGUNAAN MEDIA POWERPOINT DALAM PENINGKATAN KOSAKATA BAHASA INGGRIS SISWA KELAS V SD NEGERI 2 KASEGERAN - febriana, liyana (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Oleh:Liyana Febriani1, Imam Suyanto2, Joharman3FKIP, PGSD Universitas Sebelas Maret1 Mahasiswa S1 PGSD FKIP UNS 2, 3 Dosen S1 PGSD FKIP UNSe-mail: lovelyblue_angels@yahoo.co.id Abstract: The Use of PowerPoint Media in Improving English Vocabulary Learning at the Fifth Grade Students of SDN 2 Kasegeran in Academic Year 2013/2014. This research is Classroom Action Research (CAR) that aims to (1) describe the appropriate steps in the use of PowerPoint media in improving English vocabulary at the fifth grade students of SDN 2 Kasegeran in academic year 2013/2014, (2) describe that the use of PowerPoint media can improve English vocabulary learning at the fifth grade students of SDN 2 Kasegeran in academic year 2013/2014. The research was conducted in three cycles, with each cycle consisting of planning, action, observation, and reflection. The results showed that: (1) the appropriate steps in the use of PowerPoint media can be implemented according to the scenario, (2) the use of PowerPoint media can improve English vocabulary learning at the fifth grade students of SDN 2 Kasegeran in academic year 2013/2014. Keywords: PowerPoint, media, vocabulary, English Abstrak: Penggunaan Media PowerPoint dalam Peningkatan Pembelajaran Kosakata Bahasa Inggris Siswa Kelas V SDN 2 Kasegeran Tahun Ajaran 2013-2014. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk (1) mendeskripsikan langkah-langkah yang tepat penggunaan media PowerPoint dalam peningkatan pembelajaran kosakata Bahasa Inggris kelas V SDN 2 Kasegeran Tahun Ajaran 2013-2014, (2) mendeskripsikan bahwa penggunaan media PowerPoint dapat meningkatkan pembelajaran kosakata Bahasa Inggris siswa kelas V SDN 2 Kasegeran Tahun Ajaran 2013-2014. Penelitian ini dilaksanakan dalam tiga siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Hasilnya menunjukkan bahwa: (1) langkah-langkah yang tepat penggunaan media PowerPoint dapat berjalan sesuai skenario, (2) penggunaan media PowerPoint dapat meningkatkan pembelajaran kosakata Bahasa Inggris siswa kelas V SDN 2 Kasegeran Tahun ajaran 2013-2014. Kata Kunci: media, PowerPoint, kosakata, Bahasa Inggris